1993
DOI: 10.1146/annurev.mi.47.100193.001035
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Genetic Elements and Their Use in Biological Containment of Bacteria

Abstract: The potential risks of unintentional releases of genetically modified organisms, and the lack of predictable behavior of these in the environment, are the subject of considerable concern. This concern is accentuated in connection with the next phase of gene technology comprising deliberate releases. The possibilities of reducing such potential risks and increasing the predictability of the organisms are discussed for genetically engineered bacteria. Different approaches towards designing disabled strains witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
93
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 27 publications
0
93
0
Order By: Relevance
“…Because of its assumed importance in environmental settings (55), the focus was on conjugal plasmid transfer. Although examination of gene flow in natural microbial communities is experimentally difficult, several studies have demonstrated the occurrence of horizontal gene transfer in a variety of settings such as fresh waters (3,21) and soils (24,28,32). However, essentially no studies on horizontal gene transfer in subsurface microbial communities have been reported.…”
mentioning
confidence: 99%
“…Because of its assumed importance in environmental settings (55), the focus was on conjugal plasmid transfer. Although examination of gene flow in natural microbial communities is experimentally difficult, several studies have demonstrated the occurrence of horizontal gene transfer in a variety of settings such as fresh waters (3,21) and soils (24,28,32). However, essentially no studies on horizontal gene transfer in subsurface microbial communities have been reported.…”
mentioning
confidence: 99%
“…Recently, some procaryotic and viral genes have been shown to be able to induce tumour cell death (Martin et al, 2000;Zhuang et al, 1995;Paulus et al, 1997). In this connection, the gef gene shows a killing function in procaryotic cells, which may be modulated by the action of different promoters (Molin et al, 1993). The product of the gef gene is a cytoplasmatic membrane protein whose 19 Nterminal hydrophobic amino acids constitute a membranespanning segment, probably in the form of an alpha-helix structure that anchors the protein to the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis experiments with Gef showed that the periplasmic portion of the gene encodes the toxic domain, and that dimerisation is not essential for the toxic effect (Poulsen et al, 1991). This effect was expressed in analyses with suicide cassettes consisting of members of the gef gene family in combination with inducible promoters (Molin et al, 1993). This gene, currently being studied to determine its ability to control bacterial population death (Ronchel and Ramos, 2001), may be a new candidate for therapeutic applications.…”
mentioning
confidence: 99%
“…Therefore, LlaIR ϩ -based suicide systems could be widely exploited as a phage defense strategy if combined with a suitable phage-inducible promoter. Numerous types of conditional-suicide systems in which potent killing genes are coupled to inducible expression signals have been developed (37). The combinations are designed not to interfere with normal growth, and expression occurs under very specific conditions defined by the physical or chemical composition of the environment.…”
Section: Discussionmentioning
confidence: 99%